Epidemiology of invasive respiratory disease caused by emerging non‐Aspergillus molds in lung transplant recipients. Issue 1 (3rd February 2016) - Peghin, M.; Monforte, V.; Martin‐Gomez, M.T.; Ruiz‐Camps, I.; Berastegui, C.; Saez, B.; Riera, J.; Solé, J.; Gavaldá, J.; Roman, A.
Abstract: Objectives: Our aim was to assess the impact of positive cultures for non‐ Aspergillus molds on the risk of progression to invasive fungal infection (IFI), and the effect of prophylactic nebulized liposomal amphotericin B (n‐LAB) on these pathogens. Methods: This was an observational study (2003–2013) including lung transplant recipients (LTR) receiving lifetime n‐LAB prophylaxis, in whom non‐ Aspergillus molds were isolated on respiratory culture before and after transplantation (minimum 1‐year follow‐up). Results: We studied 412 patients, with a mean postoperative follow‐up of 2.56 years (interquartile range 1.01–4.65). Pre‐ and post‐transplantation respiratory samples were frequently positive for non‐ Aspergillus molds (11.9% and 16.9% of LTR respectively). Post transplantation, 10 (2.42%) patients developed non‐ Aspergillus mold infection (4 Scedosporium species, 4 Purpureocillium species, 1 Penicillium species, and 1 Scopulariopsis species); 5 (1.21%) had IFI, with 60% IFI‐related mortality. Non‐ Aspergillus molds with intrinsic amphotericin B (AB) resistance were more commonly isolated in bronchoscopy samples than AB‐variably sensitive or AB‐sensitive molds (54.5% vs. 25%, P = 0.04) and were associated with a higher risk of infection (56.3% vs. 1.3%%, P < 0.01). Conclusions: In LTR undergoing n‐LAB prophylaxis, pre‐ and post‐transplantation isolation of non‐ Aspergillus molds is frequent, but IFI incidence (1.21%) is low. Purpureocillium is an emerging mold. AB‐resistant non‐ Aspergillus species were found more often in bronchoscopy samples and were associated with a higher risk of infection.